THEORETICAL FOUNDATIONS OF THE TEACHING OF THE LANDSCAPE GENRE IN VISUAL ART CLASSES IN SCHOOLS OF SPECIALIZED CULTURE AND ART - Hamidjonova Komila Davronjon qizi (Galaxy International Interdisciplinary Research Journal, 2024)
Teaching the genre of landscape and teaching general concepts of visual art in visual art classes in specialized culture and art schools. It is related to the development of contemporary art, the artist's creative search for a new meaningful idea, and the satisfaction of the spiritual and educational needs of people. Therefore, the solution of the composition of the picture, finding the complex mental state, requires the artist to reflect the problems of his daily life, to feel the inner feelings of his contemporaries, and to have a deep imagination. Regular study of the theory of visual activity is one of the main conditions for successful mastering of visual art education.